Identifying Strategies to Improve Pencak Silat Achievement : A Qualitative Study - Sherly Qutrotunaini; Limpad Nurrachmad; Khoiril Anam (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2022)
This study aimed to determine the strategy to improve Pencak Silat's achievement. This research used qualitative descriptive research involving four athletes, two coaches, and one administrator of the Indonesian Pencak Silat Association. Data collection techniques included observation, interviews, and documentation. The data validity was verified using data triangulation techniques and analyzed using data reduction, presentation, and conclusion techniques. The study's results revealed that the strategy for fostering Pencak Silat's achievement was through the formulation of a coaching program involving team formation, training programs, and funding arrangements. The achievement coaching system included three stages: massing, breeding, and achievement. Supporting factors for the coaching program included the athlete's good ability and motivation, experienced field coaches, needed facilities and infrastructure, management in carrying out duties, and sufficient funding for coaching activities. The inhibiting factors for coaching included poor scheduling of some athletes and the inability of the coach to control athletes who could not participate in combined training. This study concluded that the strategy of the Pencak Silat team in improving athlete performance was good. Based on the research results, this study suggests that the Indonesian Pencak Silat Association administrators monitor athletes and coaches directly during training. Furthermore, the coaches should monitor each athlete's physical, technical, and tactical development. Thus, athletes could improve discipline in training.